Inflection Of Students’ Vocabulary Mastery On Multiple Choice Test Students’ At Vocational High School In Bogor - Yani Octafia (BUANA ILMU, 2020)
This research aims to determine and analyze the inflection of vocabulary mastery on students’ vocational high school in Bogor. The population observed in this study was eleventh grade students of vocational schools in Bogor. In the academic year 2019/2020.The respondents in this study were students at one of the vocational schools in Bogor. This research method uses a qualitative descriptive method, the population in this study were students of class XI Sirajul Falah Vocational School in Bogor totaling 336 students. The sampling technique in this study uses a probability sampling technique. From this population 20% of the population was taken so that the total sample was 68 students. The instrument of this research is multiple choice test. Researchers ask students to answer multiple choice test on vocabulary instrument. Indicators used to determine vocabulary mastery, namely: 1) determining words that have collected meanings / synonyms, and 2) determining words that have contradictory meanings / antonyms. 3) determining words related to the spelling 4) determining the words related to grammar. This research was carried out using tests given directly to the subjects studied in the vocabulary mastery aspect given 20 questions in the form of multiple choice. Based on the data analysis, there are 68 respondents who were given 20 multiple choice questions with 4 indicators, namely the correct answer indicator and the rest are the number of respondents' wrong answers. Based on the data analysis shows that there are 84% of questions related to true and the remaining 16% of questions cannot be answered correctly by students. So it can be concluded that there is inflection vocabulary mastery on vocabulary test. Kata kunci: Vocabulary Mastery; Multiple Choice Test